A case of high-dose adenosine usage for anterior communicating artery aneurysm clip ligation: What is the dose limit for a resistant response? - Nimjee, Shahid; McDonagh, David; Agrawal, Abhishek; Britz, Gavin (Asian Journal of Neurosurgery, 2017)
Intraoperative adenosine is used to induce asystole to facilitate clip ligation of intracranial aneurysms. Typically, 5–10 mg doses are used per administration and approximately 30 mg is used for a given case. An obvious concern with using adenosine is that the patient can remain in asystole or that prolonged hypotension can result in cerebral or cardiovascular ischemia. The upper limit of adenosine administration remains unclear. We present a case of a patient with a large anterior communicating artery aneurysm requiring large doses of adenosine, far exceeding previously reported cases. The patient received a 90 mg dose of adenosine to achieve 5 s of asystole as well as 30 s of hypotension that facilitated vessel dissection and clip application. Moreover, in order to successfully clip his aneurysm, he received a total of 744 mg of adenosine. After each administration of adenosine, his heart rate and blood pressure returned to baseline without the need for chest compressions or other interventions. He tolerated the procedure and had a good neurological outcome. This case is the first report of using such a high dose of adenosine in intracranial aneurysm surgery and suggests that more aggressive administration of adenosine during aneurysm clipping is feasible. Transient hypotension, as seen in this report, can provide surgeons the crucial moments they need to safely secure an aneurysm from circulation.
Keywords: Adenosine; aneurysm; asystole; cerebral; clip; high-dose; human